Pro-environmental behaviours at work: The interactive role of norms and attitudinal ambivalence - Mouro, C. (2021)
The environmental costs arising from unsustainable production patterns have increased to the point that organisations are now expected to adopt more responsible practices. Pro-environmental behaviours (PEBs) in the workplace can significantly contribute to bettering companies’ environmental performance and sustainability transition. This research investigated the interactive role of norms and attitudes in predicting voluntary energy conservation behaviours, based on a correlational study of 189 Portuguese workers. The study examined whether perceived norm conflicts involving co‐workers, closer colleagues and leaders’ behaviours promote or hinder workers’ own PEBs and whether attitudinal ambivalence towards their organisation’s pro-environmental initiatives is a moderator of this relationship. Controlling for the effect of the pro-environmental organisational climate, the ages of employees and organisation size, the results confirm that felt ambivalence moderates the relationship between norm conflict and reported energy conservation behaviours. The findings indicate that ambivalent workers are less likely to engage in PEBs if they perceive norm conflict, that is, if other staff members are not equally motivated to adopt those behaviours. Conversely, norm conflict had an energising effect on non-ambivalent workers. The results thus indicate that organisations could benefit from promoting their environmental policies more explicitly, encouraging their employees to discuss these initiatives and making voluntary PEBs more visible in the workplace.